1984
DOI: 10.1159/000269921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus Immunotherapy (Gynatren/SolcoTrichovac) on Vaginal Microflora when Used for the Prophylaxis and Treatment of Vaginitis

Abstract: In an open clinical trial 94 women with recurrent bacterial vaginitis were treated with the immunotherapeutic Gynatren/SolcoTrichovac. Vaginal flora was examined before, during and 4 weeks after completion of the vaccination. Significant reduction in the amounts of Escherichia coli, Streptococcus B, Enterococci, Bactewides, Gardnerella vaginalis as well as aberrant lactobacilli was observed. On the other hand Döderlein bacilli, normal residents of the vagina, which were found to be absent in 70 % and reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Harris [8] reported that 95% of his patients with vaginitis (86 out of 90) became free of symptoms 4 weeks after the administration of the 3rd of 3 injections; these results were obtained in a patient population suffering mainly from Gardnerella vaginitis. In contrast, Karkut [9], studying a patient population with vaginitis of various origins (G. vaginalis, Streptococcus B, enterococci, Bacteroides and Fusobacteria), reported a somewhat different result: out of 82 patients under study 33 (40%) were completely cured and 9 (11%) showed 'great improvement' 4 weeks after completion of the immunization programme.…”
Section: Discussionmentioning
confidence: 93%
“…Harris [8] reported that 95% of his patients with vaginitis (86 out of 90) became free of symptoms 4 weeks after the administration of the 3rd of 3 injections; these results were obtained in a patient population suffering mainly from Gardnerella vaginitis. In contrast, Karkut [9], studying a patient population with vaginitis of various origins (G. vaginalis, Streptococcus B, enterococci, Bacteroides and Fusobacteria), reported a somewhat different result: out of 82 patients under study 33 (40%) were completely cured and 9 (11%) showed 'great improvement' 4 weeks after completion of the immunization programme.…”
Section: Discussionmentioning
confidence: 93%